Diagnóstico arquivístico: estudo de caso no Arquivo Geral da Universidade Federal do Rio Grande do Norte - Ramalho, Sthone Arruda Neves (2019)
The Federal University of Rio Grande do Norte has been producing and accumulating over the years a large volume of information that reflects its organizational structure. This makes a large number of records. The aim of this research was to develop an archival diagnosis of the General Archive of UFRN. In order to achieve this it was developed a theoretical reflection about Archivology concepts and principles, also about university archives as specialized archives; an overview of record management considering international context and Brazilian scenario was presented and some considerations about file diagnosis and their relevance to record management were set. This work consists of a descriptive and applied research with qualitative and quantitative approach, conducted through a case study. Participant observation and semistructured interview were carried out. It was observed that the practices and procedures related to record management in the General Archives are not in full compliance with the archival precepts. Other elements also differed with what is considered ideal for a central file unit. Moreover problems were identified in physical structure, records organization and in limitation of technical staff. In order to remedy some of those problems and to promote improvements in procedures and techniques, an intervention proposal was made in the form of recommendations.